State neutrality: the sacred, the secular and equality law - O'Halloran, Kerry (Cambridge University Press, 2021)
"considers the similarities and differences in the relationship between Church and State, on a range of contemporary matters, in six countries. These - the Part II jurisdictions - are chosen on the basis of the contrasts they offer: the US and Canada, built on the contribution of immigrants but with sizeable indigenous populations, have distinctively different constitutional interpretations of that relationship; England and Wales and its five centuries of an 'established Church'; France where laïcité resolutely dictates the place of religion; Germany which struggles to overcome its Nazi past and re-integrate its eastern Communist citizens; and the outlier, Israel "a Jewish State for a Jewish people", established and maintained to provide a distinctly non-neutral protection to a specific religion and one where Judaism and the State are, seemingly, moving ever closer to a theocratic relationship. All six jurisdictions are modern democracies and all are signatory nations to international treaties that require States to adopt a neutral approach to religion"--